Effect of trisilanol isobutyl polyhedral oligomeric silsesquioxane (TPOSS) in recycled PET (rPET) and polypropylene based compound: Investigation on mechanical properties - PHUMMA, Rujira; VANICHVATTANADECHA, Chutima; UMMARTYOTIN, Sarute (Journal of Metals, Materials and Minerals, 2023)
Recycled polyethylene terephthalate is successfully prepared. This project is involved for “Circular economy” policy. It is successfully prepared into powder form by nano-grinder technique. 10 phr of PP-g-MA and 1 phr to 5 phr of TPOSS are added for compatibilizer and mechanical properties enhancement, respectively. PP-g-MA can form the chemical linkage of the anhydride groups with the polyamide end groups. 20 wt% of recycled polyethylene terephthalate powder and polypropylene based compound is successfully fabricated by melt mixing. Then, it is fabricated by melting spinning technique. Fourier transform infrared presents Si-O-Si linkage in binary blend compound. X-ray diffraction pattern reports that single phase is obtained. Adding TPOSS can be induced to crystallinity enhancement. No significant change of thermal properties was observed from room temperature to 300℃. Scanning electron microscope reports that with the PP-g-MA provides smoothness of surface. Recycled polyethylene terephthalate is uniformly distributed. Melting and crystallization temperatures are reported to be 162℃ to 167℃ and 115℃ to 120℃, respectively. All of throughput rate is reported to be 1.8 g⸳min-1 to 2.3 g⸳min-1. With the existence of TPOSS, the mechanical properties of compound are slightly increased. TPOSS are added for mechanical properties enhancement. The polymer compound presents the excellent properties. It is remarkable to note that recycled polyethylene terephthalate is considered as an excellent candidate for use as raw material for polymer compound production.